The poverty of riches : St. Francis of Assisi reconsidered - Wolf, Kenneth Baxter, 1957- (Oxford studies in historical theology., 2005)
Saint Francis of Assisi is arguably the most attractive saint ever produced by the Catholic Church. The unusually high regard with which he is held has served to insulate him from any real criticism of the kind of sanctity that he embodied: sanctity based first and foremost on his deliberatepursuit of poverty. In this book, Kenneth Baxter Wolf takes a fresh look at Francis and the idea of voluntary poverty as a basis for Christian perfection. Wolf's point of departure is a series of simple but hitherto unasked questions about the precise nature of Francis's poverty: How did he go abouttransforming himself from a rich man to a poor one? How successful was this transformation? How did his self-imposed poverty compare to the involuntary poverty of those he met in and around Assisi? What did poor people of this type get out of their contact with Francis? What did Francis get out ofhis contact with them? Wolf finds that while Francis's conception of poverty as a spiritual discipline may have opened the door to salvation for wealthy Christians like himself, it effectively precluded the idea that the poor could use their own involuntary poverty as a path to heaven. Based on athorough reconsideration of the earliest biographies of the saint, as well as Francis's own writings, Wolf's work sheds important new light on the inherent ironies of poverty as a spiritual discipline and its relationship to poverty as a socio-economic affliction.